Riesgo de inundación por escorrentías superficiales en zonas pobladas del sector calichana, parroquia buenavista, cantón pasaje, provincia del oro. - Zumba Perea, Fausto Alexander (2017)
In the last few years in the countries the temperature worldwide has increased. This indicates that the warming of the planet comes accelerate, which increases the probability of occurrence of intense meteorological phenomena such as droughts, storms and floods. This process directly influences something negative for hydrological watersheds, which leads to the coupling of hydrological, hydraulic and geographic information tools and spatial analysis, which clump the physical characteristics of the watershed and Allow you to perform reliable analyses. Today, however, digital terrain models and the physical-characteristics maps of watersheds in digital format provide information that can be processed more effectively. Over the past five decades, flood events have been responsible for more than half of the total cost of natural disasters in the world, posing new challenges in the planning of hydraulic resources and risk management of social impact. In the equatorial zone of the American continent there are climatic variations that do not obey the same processes observed in the high latitudes responsible for the seasons, due to the climate is affected by slight variations that allow to identify two Climatic periods known as dry season and rainy season. Due to the alteration of climatic conditions, phenomena such as "El Niño" and "La Niña", which are characterized by deficits and excess rainfall, are presented, respectively. Proposals for rainfall at risk of floods due to surface runoff in populated areas requires the integration and coupling of hydrological, hydraulic and geographic information tools and spatial analysis, which clump the Physical characteristics of the watershed and allow for reliable analysis. Today, however, digital terrain models and the physical-characteristics maps of watersheds in digital format provide information that can be processed more effectively. The present study will take into account the problems caused by natural disasters, applying hydraulic and hydrological processes to look for successful solutions, and be able to unite these criteria in appropriate ways. The objective is to develop a methodology for the risk of flooding by surface runoff and to determine and implement a hydraulic system that can provide digital geographic information to determine those sectors that are vulnerable to Floods. This research was conducted at the site Calichana, Buenavista Parish, Pasaje Canton, province of Gold, with the foundation of implementing mathematical model HEC-RAS for the system formed by the river Calichana to the right margin. The main flood zones have been identified by simulating scenarios. In order to obtain the rainfall of design by means of the application of hydrological model will proceed to obtain the maximum flows of floods generated by hydrologic modeling mathematical for the storms of recurrences 5, 10, 25, 50 and 100 years extracted from the ¨ Storms of project in bases to the meteorological stations: M-747 RIO CHICO, M-040 passage, M-481 the future, based on topographic processes, obtaining to make within the geographic Information System (SIG), a digital model of elevations (MDE), which It serves as a basis for both the extraction of attributes and the dump of results. The (SIG) is a system capable of integrating, storing, editing, analyzing, sharing and displaying geographic information and its associated attributes. Among the most widespread applications are ArcView GIS, ArcGis, ILWIS and Idrisi among others. Due to the risk index of the product that causes floods and dangerousness, exposure and vulnerability, reliable methodologies must be implemented, for which data bank must be counted, which allow us to analyze the most crucial conditions to which can expose the system these sectors, in rough terrain and with very strong slopes. Ensuring constant and permanent operation during its period of returns (Tr).